Proton ordering model of phase transitions in hydrogen bonded ferrielectric type systems: the GPI crystal - Stasyuk, I.; Czapla, Z.; Dacko, S.; Velychko, O. (Condensed Matter Physics, 2003)
A microscopic model based on the consideration of the proton ordering is
proposed for describing the H-bonded ferroelectric crystalline systems with
a complex structure of the hydrogen bond network. The model has been
used for the investigation of thermodynamics and dielectric properties of
the GPI crystal. The symmetry analysis of the order parameters responsible
for the mixed (ferro- and antiferroelectric) nature of ordering is performed
within the model. The phase transition into the ferroelectric state is
described. Changes in the dielectric susceptibility of the crystal are studied
in the presence of the transverse external electric field acting along the c -
axis. The results of measurements of temperature and field dependences
of dielectric permittivity ε'c
in the paraelectric phase are presented. The
microscopic mechanism of the observed effects is discussed based on the
comparison of theoretical results and experimental data. A conclusion is
made about the significant role of the ionic groups connected by hydrogen
bonds in the charge transfer. So they make an important contribution into
the polarizability of the GPI crystal along the direction of H-bonded chains. Для опису сегнетоелектричних водневозв’язаних кристалічних систем із складною структурою сітки водневих зв’язків запропоновано мікроскопічну модель, яка базується на врахуванні впорядкування протонів. Її застосовано для дослідження термодинаміки і діeлектричних властивостей кристалу GPI. В рамках моделі дано симетричний аналіз параметрів порядку, відповідальних за змішаний
(сегнето- і антисегнетоелектричний) характер впорядкувань. Описано фазовий перехід до сегнетоелектричного стану та вивчено зміни
у діелектричній сприйнятливості кристалу при наявності зовнішнього поперечного електричного поля прикладеного вздовж c -осі. Наведено результат вимірювань температурних і польових залежностей діелектричної проникності ε'c у параелектричній фазі. На основі
порівняння теоретичних результатів і даних експерименту обговорюється мікроскопічний механізм спостережуваних ефектів. Зроблено висновок про важливу роль іонних груп, з’єднаних водневими
зв’язками, у переносі заряду. Вони дають вагомий внесок до поляризованості кристалу GPI у напрямку вздовж ланцюжків водневих
зв’язків.